2018
DOI: 10.1158/1535-7163.mct-17-0472
|View full text |Cite
|
Sign up to set email alerts
|

ALK Inhibitor Response in Melanomas Expressing EML4-ALK Fusions and Alternate ALK Isoforms

Abstract: Oncogenic fusions occur in several types of cancer and can be effectively treated with ALK inhibitors; however, fusions and treatment response have not been characterized in malignant melanomas. Recently, a novel isoform of ( ) was reported in 11% of melanomas but the response of melanomas expressing to ALK inhibition has not been well characterized. We analyzed 45 melanoma patient-derived xenograft models for mRNA and protein expression. expression was identified in 11 of 45 (24.4%) melanomas. Ten melanomas e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 33 publications
2
36
0
4
Order By: Relevance
“…Cell lines were verified by short tandem repeat analysis and BRAF and NRAS mutation status was determined using the COSMIC database (34,35). MB2141, MB2204, and MB2724 were derived as previously described (36). Cell lines were tested for Mycoplasma contamination using a PCR-Based Kit (ATCC) and confirmed negative within 20 passages or 3 months before use.…”
Section: Methodsmentioning
confidence: 99%
“…Cell lines were verified by short tandem repeat analysis and BRAF and NRAS mutation status was determined using the COSMIC database (34,35). MB2141, MB2204, and MB2724 were derived as previously described (36). Cell lines were tested for Mycoplasma contamination using a PCR-Based Kit (ATCC) and confirmed negative within 20 passages or 3 months before use.…”
Section: Methodsmentioning
confidence: 99%
“…15 Subsequent studies have reported ALK ATI expression in 0-15.6% of metastatic melanomas. 24,25 Interestingly, Uguen et al identified that 0% of cases showed IHC expression in a prospective series of 133 patients' metastases. 24 This may be due to regional variations, as noted in the manuscript; however, it is of note that the authors used a different ALK IHC antibody (5A4 clone).…”
Section: Discussionmentioning
confidence: 99%
“…ALK was fi rst identifi ed as the protein product of an abnormal fusion gene produced by a specifi c chromosomal translocation in anaplastic large cell lymphoma (21). Later, it was identifi ed in other neoplasms, either benign or malignant, such as lung adenocarcinoma, Ewing sarcoma, infl ammatory myofbroblastic tumor, epithelioid fi brous histiocytomas (22). ALK was also detected in approximately 10-15% of all spitzoid tumors; ALK fusions are found in benign Spitz naevi, atypical Spitz tumors, and less commonly in spitzoid melanoma (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%